Combination of Herbal Steam Bath and Endorphin Massage to Increasing Breast Milk Production - Shinta Wurdiana Rhomadona; Dianita Primihastuti (Journal of Midwifery, 2023)
The importance of breastfeeding has strong evidence. Complementary therapy that can increase milk production is to increase comfort and body fitness by using herbal steam baths. This is local wisdom that is still preserved in Indonesia as a therapy for postpartum mothers with water vapor. Another similar alternative is endorphin massage, which is a light touch therapy on the neck, back and arms that can trigger the release of endorphins that affect milk production. The purpose of this study was to estimate that the combination of the two methods would be more effective in influencing breast milk production. This research design is a quasi-experimental. The population in this study were postpartum mothers at the Independent Practice Midwife in Surabaya with a total sample of 40 which were divided into treatment and control groups, using purposive sampling technique. The treatment group was given intervention with a combination of herbal steam baths 2x/week for 5-20 minutes and endorphin massage 2x/week for 20 minutes, while the control group was not given. Each group was given a pre-test and post-test to determine the volume of breast milk production with indicators of increased baby weight, increased frequency of urination and defecation. Statistical test using Mann Whitney and Shapiro Wilk. The results showed that there was a significant effect of the combination of herbal steam baths and endorphin massage on increasing breast milk production with a value of Î± =0,000 atau Î± <0,05. There was a significant difference in milk production in the treatment group compared to the control group with a value of Î± =0,000 atau Î± <0,05. Conclusion: By doing a combination of herbal steam baths and endorphin massage regularly, it can increase milk production.